Evaluation of the functional capacity of elderly people in a community of the municipal district of Moreno – PE - Maria Emília Vilela Tenório; Maria Janaína Melo dos Santos; Thereza Cristina Silva de Sena; Silvana Sidney Costa Santos; Nara Carneiro Lacerda (Rev Rene)
The objective of this study was to evaluate the functional capacity of the elderly. This descriptive research was accomplished in the Community Alto das Estrelas, Moreno-PE, with 30 elderly people registered at the PSF. A form divided by 3 parts was used for the data collection: the senior’s identification; Scale of Daily Life Activities (DLA) and Scale of Instrumental Activities of Daily Life (SIADL); identification of the causes of the senior’s incapacities, whose application was made through domiciliary visits. The results obtained were the following: 16 women and 14 men; aged 60 – 70 years; farmers, married, retired or pensioners; illiterates; living with children and grandchildren, who they support; accomplishing leisure and religious activities. Their main complaints concerning health are: "forgetfulness" and visual alterations. Three of them were dependent of other people’s help, due to: sequel of Cerebral Vascular Accident, osteoarticular disease and psychiatric disease. It was elaborated a rehabilitation proposal as well as maintenance of the ‘ functional capacity assisted at the USF.